Enhanced SIRT3 expression restores mitochondrial quality control mechanism to reverse osteogenic impairment in type 2 diabetes mellitus - Yansi Xian; Bin Liu; Tao Shen; Lin Yang; Rui Peng; Hongdou Shen; Xueying An; Yutian Wang; Yu Ben; Qing Jiang; Baosheng Guo (Bone Research)
Abstract Osteoporosis represents a prevalent and debilitating comorbidity in patients diagnosed with type 2 diabetes mellitus (T2DM), which is characterized by suppressed osteoblast function and disrupted bone microarchitecture. In this study, we utilized male C57BL/6 J mice to investigate the role of SIRT3 in T2DM. Decreased SIRT3 expression and impaired mitochondrial quality control mechanism are observed in both in vitro and in vivo models of T2DM. Mechanistically, SIRT3 suppression results in hyperacetylation of FOXO3, hindering the activation of the PINK1/PRKN mediated mitophagy pathway and resulting in accumulation of dysfunctional mitochondria. Genetical overexpression or pharmacological activation of SIRT3 restores deacetylation status of FOXO3, thus facilitating mitophagy and ameliorating osteogenic impairment in T2DM. Collectively, our findings highlight the fundamental regulatory function of SIRT3 in mitochondrial quality control, crucial for maintaining bone homeostasis in T2DM. These insights not only enhance our understanding of the molecular mechanisms underlying diabetic osteoporosis but also identify SIRT3 as a promising therapeutic target for diabetic osteoporosis.